Tantangan dan Implikasi dalam Dunia Korporasi Modern - Diva Dinar Fasya (As-Syirkah: Islamic Economic & Financial Journal, 2025)
Globalization, business complexity, and increasing demands for transparency have placed business ethics, law, and corporate governance as strategic issues in maintaining business continuity. Major scandals such as those of Enron, Lehman Brothers, Jiwasraya, and Garuda Indonesia demonstrate that weak ethical practices and oversight mechanisms can damage reputations, undermine public trust, and threaten economic stability. This study uses a qualitative methodology based on literature studies with secondary data to examine corporate scandals, practices in Indonesia, and global challenges such as technological disruption, regulatory differences, and demands for sustainability. The results confirm that the integration of ethics, law, and governance is a crucial foundation for corporate sustainability, which is not solely profit-oriented but also social and environmental responsibility. To achieve this, companies need to strengthen internal and external oversight through independent audits, professional audit committees, whistleblowing mechanisms, and build a culture of ethics through codes of conduct, training, and leadership role models. Meanwhile, the government must enforce laws consistently and adapt to technological developments and global markets. This synergy is key to maintaining reputations, increasing competitiveness, and creating long-term value for all stakeholders.